Influence au nanoparticles on absorption and luminescent properties rhodamin c in ethanol - Aimukhanov, A.K.; Esimbek, A.M.; Ibrayev, N.Kh. (Publishing House of the KarSU named after E.A.Buketov, 2016)
Au nanoparticles were obtained gold target ablation in ethanol second harmonic of solid state laser 215 LQ. The concentration of nanoparticles (NPs) Au was determined to change the target weight before and after ablation by duration of 30 minutes. Studies have shown that by adding Au nanoparticles by C = 5 * 10- 6 mol / l solution of dye, the optical density at the absorption maximum is increased. Fluorescence intensity at the maximum increases 1.2 times. The provisions of maxima of the bands and their half-widths are not changed.
Keywords: laser ablation; gold nanoparticles; local plasmon resonance; absorption optical density; fluorescence intensit y; stimulated emission; the pulse width generation